Total Harmonic Distortion Measurement of 13-level FCML Inverter for SPWM and THIPWM Method - BHADRA Ananta Bijoy (Journal of Electrical and Electronics Engineering, 2022)
One of the main problems for flying capacitor multilevel (FCML) inverter is the higher value of total harmonic distortion (THD) with number of capacitors and switching devices. No step has been taken to consider sinusoidal pulse width modulation (SPWM) and third harmonic injection pulse width modulation (THIPWM) techniques with carrier phase disposition (PD) for THD analysis of 13-level FCML inverter. This paper proposes the comparative study of these two PWM techniques with carrier PD to obtain the lowest THD for inverter. The proposed system is simulated and analyzed in MATLAB/SIMULINK environment. The results from this analysis show the optimal value of amplitude and frequency modulation index in which lowest THD is obtained for FCML.